Deadly headache: Mirror aneurysm about a case report - Dávila hernández, Carlos Alberto (2022)
Introduction: Intracerebral aneurysms are incidental findings in imaging studies performed for other diagnoses. Case Report: 35-year-old female patient, who presented syncope after severe headache without yielding to conventional treatment with NSAIDs; with a history of long-standing headache and sporadic treatment. On examination: neurological: awake, facial asymmetry, dysarthria, decreased muscle strength in both lower limbs, no meningeal signs; the brain tomographic report without contrast indicated: expansive brain lesions of etiology to be determined at both sides of the diencephalon: rule out glioma vs aneurysms; cerebral Angiotac with contrast, reflects bilateral intracranial internal carotid and middle cerebral (mirror) aneurysms. Subsequently the patient was evaluated by the neurosurgeon on duty, who indicated to refer to a center of higher complexity, for not having the necessary instruments for surgery; patient died on the way to the referral center.  Conclusions: Being a rare pathology, it is not considered as a first option for diagnostic suspicion after a headache event.